The Effectiveness of MONOGAMIA (Monopoly to Prevent Anemia) on Female Adolescent Knowledge about Anemia Prevention and Consumption of Iron Supplement - Nurannisa Fitria Aprianti; Apriani Susmita Sari (Babali Health, 2024)
Background: The main causes of anaemia in female adolescents are iron and nutrient deficiencies, excessive blood loss during menstruation and incorrect diet due to lack of knowledge of female adolescents about prevention of anaemia and consumption of iron supplement tablets. This study aims to analyse the effectiveness of MONOGAMIA on the level of knowledge of female adolescents. Methods: The research design is a quasi-experiment pretest and post-test with control group. The sample amounted to 96 Female Students divided into 2 groups, at Senior High School East Lombok, from October 4-14th, 2024. The intervention group was educated with MONOGAMIA and control group used CEMARI Flip Chart, then Fe tablet given for 4 weeks. The data collection used questionnaires of knowledge and iron supplement consumption compliance cards. Pre-test and post-test of knowledge was taken in the same day in both group, compliance of iron consumption taken 1 week after education. The research data were analysed using Wilcoxon, Mann Whitney, and Chi-Square (α<0.05). Results: There was a significant difference of knowledge about anaemia prevention before and after education in both groups (p=0.000; p=0.000). There was a significant difference of knowledge about anaemia prevention after education between two groups (p = 0.000). There was a significant difference of iron supplement consumption between intervention and control group after education (p = 0.028). Conclusion: MONOGAMIA is more effective in increasing of knowledge about anaemia prevention and iron supplement consumption in female adolescent than CEMARI. MONOGAMIA can be used to educate female adolescent to prevent anaemia